TINGKAT KECEMASAN PESERTA DIDIK PADA PEMBELAJARAN KAYANG DI SMP ISLAM BAWARI PONTIANAK - Fathurrozi Fathurrozi; Andika Triansyah; Fitriana Puspa Hidasari (Universitas Tanjungpura, 2020)
AbstrackThis research is motivated by many students who feel anxious, tense, afraid, and do not want to do the kayang movements during kayang learning at school. Students are hesitant and also often say can not be done before the movement kayang. The goal to be achieved is to find out how high the level of anxiety of seventh grade students of Pontianak Islamic Bawari Middle School towards kayang learning.This research is descriptive research. The method used is a survey with data collection techniques using a questionnaire. The population in this study were all students of class VII Islamic Middle School Bawari Pontianak, the sampling technique used was purposive sampling. The sample used was class VII students, amounting to 69 students. The results showed that the anxiety level of students in kayang learning in Bawari Pontianak Islamic Middle School was in the category of